Peningkatan Pengetahuan Dengan Metode Terapi Kelompok Pada Ibu Menyusui Di RW 12 Wonorejo Gondangrejo Karanganyar - Ernawati; Widyastuti , Deny Eka; Umarianti , Tresia; Rohmatika, Dheny (PENA ABDIMAS : Jurnal Pengabdian Masyarakat, 2025)
Breastfeeding is a natural process that is not easy. Exclusive breastfeeding coverage is not free from problems that arise during the breastfeeding process, including the misconception that breast milk production is low or insufficient for the baby's needs. This condition is caused by several factors, including the mother's food and drink intake, the mother's psychological or emotional state, and abnormal breast shape. Group therapies to reduce depression include psychoeducational groups, support groups, and self-help groups. The objective was to determine the increase in knowledge through group therapy among breastfeeding mothers in RW 12 Wonorejo, Gondangrejo, Karanganyar. The method used emphasized material on increasing knowledge through group therapy. The results showed that breastfeeding mothers in RW 12 improved their understanding of group therapy and gained more experience with problems encountered by breastfeeding mothers. There was a 0.31% increase in knowledge through group therapy. Keywords: Knowledge, breastfeeding, breast milk, postpartum mothers